2021
DOI: 10.21203/rs.3.rs-420929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Young Male with a Non-ST Elevation Myocardial Infarction and Polycythemia Vera

Abstract: Polycythemia Vera (PV) is a clonal myeloproliferative disease characterized by an erythroid dominant trilineage proliferation of hematopoietic precursor cells. Acute coronary syndrome is known to occur in patients with PV. However, there are very rare reported cases of myocardial infarction upon the initial presentation of PV. We present such a case of a 37 years old male, with no known cardiovascular risk factors, who had an initial presentation of NSTEMI treated with drug eluting stent (DES). Later investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another report by Malak et al concluded that 4% of all patients with myeloproliferative disorder die from MI [5]. Cardiac challenges in patients with PV include MI, in-stent restenosis [6], and progressive ischemic heart failure [7]. Atrial fibrillation (A-fib) is the most prevalent sustained arrhythmia, affecting up to 1% of the world's population [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another report by Malak et al concluded that 4% of all patients with myeloproliferative disorder die from MI [5]. Cardiac challenges in patients with PV include MI, in-stent restenosis [6], and progressive ischemic heart failure [7]. Atrial fibrillation (A-fib) is the most prevalent sustained arrhythmia, affecting up to 1% of the world's population [8].…”
Section: Introductionmentioning
confidence: 99%